Effects of recombination rate on human endogenous retrovirus fixation and persistence. - Katzourakis, A; Pereira, V; Tristem, M (2007)
Endogenous retroviruses (ERVs) result from germ line infections by exogenous retroviruses. They can proliferate within the genome of their host species until they are either inactivated by mutation or removed by recombinational deletion. ERVs belong to a diverse group of mobile genetic elements collectively termed transposable elements (TEs). Numerous studies have attempted to elucidate the factors determining the genomic distribution and persistence of TEs. Here we show that, within humans, gene density and not recombination rate correlates with fixation of endogenous retroviruses, whereas the local recombination rate determines their persistence in a full-length state. Recombination does not appear to influence fixation either via the ectopic exchange model or by indirect models based on the efficacy of selection. We propose a model linking rates of meiotic recombination to the probability of recombinational deletion to explain the effect of recombination rate on persistence. Chromosomes 19 and Y are exceptions, possessing more elements than other regions, and we suggest this is due to low gene density and elevated rates of human ERV integration in males for chromosome Y and segmental duplication for chromosome 19.